Visual Media Practices Reshape Diagnostic Observation and Patient Care in Medical Training Contexts - Adjeketa, Blessing; Adjeketa, Theophilus; Adjeketa, Hezekiah (Universitas Negeri Surabaya, 2026)
In the 21st century, diagnostic care is often associated with biotechnological advancement, overlooking the importance of clinicians’ observational skills. Visual literacy—the ability to interpret and create meaning from images—is therefore a core clinical competence. Between November 2025 and January 2026, this study engaged 35 caregiving students from five private hospitals in Sapele, Delta State, focusing on the visual identification of jaundice. Using a conceptual literature review, the study integrates visual pedagogical frameworks, such as visual thinking strategies, with medical humanities curricula. It examines how visual narratives and films contribute to improved diagnostic accuracy and compassionate care. Findings suggest that structured exposure to visual arts enhances critical observation and reduces cognitive bias, while film-based learning helps clinicians recognize non-verbal cues, environmental context, and unspoken symptoms. Incorporating visual literacy into medical training improves the interpretation of patient data and supports a more humanistic approach to care. The study concludes that visual literacy should be formalized as a clinical skill, and recommends integrating film-based modules into medical curricula to bridge the gap between technical expertise and observational competence for better diagnostic and therapeutic outcomes